Ten new Bacillariophyta species from James Ross Island and the South Shetland Islands (Maritime Antarctic Region) - Zidarova, Ralitsa; Kopalová, Kateřina; van De Vijver, Bart (Phytotaxa, 2016)
The present paper describes 10 new diatom (Bacillariophyta) species from the Maritime Antarctic Region. Five of the newly described taxa: Caloneis australis sp. nov., Mayamaea sweetloveana sp. nov., Navicula romanedwardii sp. nov., Sellaphora antarctica sp. nov. and Sellaphora gracillima sp. nov. have been previously reported from the Antarctic Region but were force-fitted into incorrect names. Five other taxa: Chamaepinnularia elliptica sp. nov., Cosmioneis regigeorgiensis sp. nov., Mayamaea tytgatiana sp. nov., Muelleria pimpireviana sp. nov. and Pinnularia pinseeliana sp. nov. are newly discovered taxa. The morphology of all new species is studied using both light and scanning electon microscope observations and compared with similar species from the Antarctic Region and worldwide. Data about the ecology and confirmed Antarctic distribution of the new species are added.